FROM THE CONTINUING SOURCES: THE INSTITUTE OF UKRAINIAN STUDIES OF VASYL STEFANYK PRECARPATHIAN NATIONAL UNIVERSITY THROUGH THE PRISM OF TIME - Greshchuk, Vasyl; Greshchuk, Valentyna (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article examines the history of the foundation, formation and fruitful creative work in the field of Ukrainian studies of the Educational and Scientific Institute of Ukrainian Studies at Vasyl Stefanyk Precarpathian National University. The purpose of the article is to highlight the history of the development of Ukrainian studies and significant achievements in the field of Ukrainian studies at the Educational and Scientific Institute of Ukrainian Studies at Vasyl Stefanyk Precarpathian National University, the value of such educational and scientific institutions in the development and improvement of research work at the university, drawing attention to the need for their expansion and elevation of the role in today’s difficult conditions of higher education reform. Under such conditions, the analytical-descriptive method becomes productive in such studies. The result of the scientific study was an understanding of the history of the formation and development of the educational and scientific Institute of Ukrainian Studies at Vasyl Stefanyk Precarpathian National University, as well as an outline of the prospects of its activity in the near future. The conducted study proved that the appearance of such a unit in the structure of the university was caused by a radical change in social and political circumstances in Ukraine in the 90s of the last century, by its gaining of independence. This required Ukrainian studies, which in the conditions of Soviet totalitarianism acquired distorted forms caused by manipulative pseudo-theories, neglect of real facts, events, their distortion and falsifications, to study Ukrainian studies issues on a scientific and objective basis. The article analyzes the multifaceted activities of the Institute, special attention is paid to the preparation for printing and publication of numerous monographs, collections of scientific articles, the scientific journal "Ukrainian Studies", dictionaries, educational and methodological materials on Ukrainian studies issues. Attention is also drawn to creative relationships with well-known scientific institutions of Ukrainian studies in Ukraine and abroad. The prospects of the Institute’s activity in the nearest future are also determined. The scientific novelty of intelligence is determined by the lack of research into the activities of the educational and scientific Institute of Ukrainian Studies at the Vasyl Stefanyk Precarpathian National University and the importance of ideologically uninvolved Ukrainian studies for modern state-building. Practical meaning. The obtained results are important for the development and deepening of modern Ukrainian studies, and the activity of the Institute can serve as a model for the creation of similar educational and scientific units in other universities.